Reproductive outcomes following cesarean scar pregnancy – a case series and review of the literature. (May 2016) - Gao, Lufen; Huang, Zhongwei; Zhang, Xian; Zhou, Na; Huang, Xinke; Wang, Xiaoyu
Abstract: Objective: To assess the reproductive outcomes following cesarean scar pregnancy (CSP) in our center and review of published literature on CSP and subsequent reproductive issues. Methods: Over a 3-year period, 28 cases of CSPs were diagnosed in our hospital. Follow up data of 22 cases were available which included the gestational age at diagnosis of CSP, treatments employed and outcomes of previous cesarean scar pregnancy. We also had details on subsequent fertility outcomes in these women, which included intervals between the previous CSP and subsequent pregnancy, maternal and neonatal outcomes of these subsequent pregnancies and mode of delivery. Results: Eight women desired to conceive and amongst them, seven women manage to conceive spontaneously. There were five pregnancies delivered at term, two miscarriages and one recurrent CSP. One patient had placenta accreta diagnosed at cesarean section at term and had massive hemorrhage. The remaining 4 term pregnancies were delivered uneventfully by elective cesarean sections. The mean interval between the cesarean scar pregnancy and subsequent pregnancy was 24.6 months (range 9–48 months). One patient experienced secondary infertility and despite thorough investigations, no abnormalities were detected. One of the women who did not desire future fertility conceived spontaneously at 9 and 18 months respectively after one CSP and had induced abortions twice. There were 3 women who had uterine scar defect repaired, only 1 resulted in a live birth but had placenta accreta with a lower uterine segment defect and suffered from massive hemorrhage, one woman had a subsequent miscarriage with a diverticulum in the lower uterine segment, and one woman had unexplained secondary infertility. Conclusion: Most women were able to conceive following CSPs. Reproductive outcomes included normal intrauterine term pregnancy, miscarriage, recurrent CSP, and infertility. Placenta accreta, which could be misdiagnosed antenatally, was a serious complication in subsequent pregnancies. Diverticulum or defect in the lower uterine segment could happen after CSP. Repair of the uterine defect, following a CSP neither guaranteed the healing of the scar, nor the ability to ensure a safe pregnancy outcome. Appropriate counseling to women desiring fertility with a history of CSP is essential and once they conceive early referral to tertiary centers for follow up is pertinent.